The hunter's daughter - Solvinic, Nicola (Berkley, 2024)
"A hypnotic, sinister debut mystery about a seemingly good cop who is secretly the daughter of a notorious serial killer who must, against all the rules, insert herself into a new investigation when ritually killed bodies start appearing in her father's old territory. Anna Koray has shut the door on her past. The records of her childhood--and the troubling memories--are sealed away thanks to a controversial hypnosis treatment. She's a police lieutenant in a rural town, raising money for good causes, coaching girls' soccer, and even on-and-off dating Nick, a local ER doctor. Then she shoots a man in the line of duty and finds herself terribly drawn to him in the moment of his death. Her childhood memories return, igniting terrible dreams of her beloved father, his hands red with blood, surrounded by flower-decked corpses he had sacrificed to the god of the forest. Simultaneously, to Anna's horror and fascination, a serial killer has emerged who is copying her father. Can it be a coincidence? Is her father alive after all? Will the killer expose her, destroying everything she has built for herself, including her rekindled relationship with Nick? Does she want him to? Against all the rules Anna inserts herself into the investigation, walking a thin line between justice and protecting her secrets. But as she haunts the forest, using her father's tricks to hunt the killer, will she find what she needs most...or lose herself in the gathering darkness?"--